Micafungin Breakthrough Fungemia in Patients with Hematological Disorders: A Retrospective Study to Determine Therapeutic Strategy. (4th October 2017) - Kimura, Muneyoshi; Araoka, Hideki; Yamamoto, Hisashi; Nakamura, Shigeki; Nagi, Minoru; Yamagoe, Satoshi; Miyazaki, Yoshitsugu; Ogura, Sho; Mitsuki, Takashi; Yuasa, Mitsuhiro; Kaji, Daisuke; Kageyama, Kosei; et al.
Abstract: Background: Micafungin (MCFG) breakthrough fungemia (MBF) is recognized as a serious infection especially in high-risk patients with hematological disorders (HDs). Methods: A retrospective study of MBF among adult patients with HDs was conducted between January 2008 and June 2015. MBF was defined as fungemia in patients receiving ≥50 mg/day of MCFG for ≥3 days before the first positive blood culture. Breakthrough strains were identified by using conventional methods, r-RNA sequencing, and MALDI-TOF-MS. The drug susceptibility was determined by the broth microdilution method according to current CLSI standards. Results: Thirty-nine patients with MBF were identified. Thirty-five of the 39 patients were administered 150 mg/day of MCFG. Acute myeloid leukemia was the most common underlying HDs (27/39). The 39 causative organisms were Candida species (30), and non- Candida fungal species (9). Among the 35 stored strains, C. parapsilosis (14), Trichosporon asahii (7), C. glabrata (5), C. albicans (3), and other fungal spices (6) were identified by sequencing. Although, only 37% (11/30) of candidemia occurred during neutropenia, the majority (8/9) of non- C andida fungemia occurred during neutropenia ( P  < 0.01). T. asahii was the major cause of MBF during neutropenia (7/19). The crude 30-day mortality rate of MBF was 46% (18/39). Renal failure, steroid, hypotension, and age ≥60 were identified as independent risk factors of the crude 30-day mortality. The crude 14-day mortality rate of the patients treated by early (≤48 hours after the onset) MCFG change (EMC) to other antifungal agents was lower than those without EMC (14% vs. 43%, P = 0.044). The majority of stored strains (33/35) were correctly identified by MALDI-TOF-MS. Furthermore, 72% of the causative Candida strains were wild-type susceptibility to MCFG. Additionally, the MICs of voriconazole for T. asahii were low (ranged from 0.015 to 0.12 μg/mL), while MICs of amphotericin B for T. asahii were high (ranged from 2 to 4 μg/mL). Conclusion: MBF caused by non- Candida fungi should be considered especially during neutropenia. EMC could improve the mortality rate. According to the epidemiology and the drug susceptibility result of MBF, an empiric voriconazole-based regimen should be initiated for MBF to cover for T. asahii during neutropenia. Disclosures: All authors: No reported disclosures.